PENGUATAN KAPASITAS MASYARAKAT DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN KEPULAUAN ANAMBAS (Studi pada Pengembangan Objek Wisata Pantai Padang Melang Desa Batu Berapit Kecamatan Jemaja Tahun 2014-2016) - Arie Kurniawan Dwi Putra; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to examine the strengthening of community capacity on the development of tourism object in Padang Melang Beach, Batu Berapit Village, where to encourage acceleration of regional tourism development realized through Anambas Islands Regent Regulation No. 34.a Year 2014 on the Guidance of Tourism Destination of Excellence in Anambas Islands Article 5 paragraph (3) has determined two strategic areas namely:A. Padang Melang Beach Area in Jemaja Sub-District; B. Temburun Waterfall Area in East Siantan District. Furthermore, through the Head of Department of Tourism Ministry of Youth and Sports Ministry of Anambas Islands no. 29 of 2014 on the Establishment of Village Tourism Area Anambas Islands District is a form of community empowerment, which supports the creation of an independent community that has the capacity related to the development of attractions in Padang Melang Beach in order to achieve prosperity. In analyzing and explaining the results of this study, the authors use qualitative research and analysis in this study using qualitative data analysis. The results of research on strengthening the capacity of the community on the development of attractions in Padang Melang Beach Batu Berapit Village shows that: 1. The determinant actors in the development of tourism object in Padang Melang Beach are the Regional Government of Anambas Islands District as the makers and implementers of the policy, the private sector / capital owners as the supporting providers of resources or facilitators and the community as internal actors directly involved in tourism development. 2. Relationship Cooperation between components or the deciding actors is still less than optimal. Due to the lack of support from external actors namely the government in empowering the community and has not involved the private sector / owners of capital as a supporter that helps the problem of providers of reliable human resources and adequate funds.Keywords: Strengthening Community Capacity, Tourism Development